Complete Genome Sequence of Multiple-Antibiotic-Resistant Streptococcus parauberis Strain SPOF3K, Isolated from Diseased Olive Flounder (Paralichthys olivaceus) - Lee, Yoonhang (Genome Announc, 2018)
Here, we report the complete genome sequence of multiple-antibiotic-resistant Streptococcus parauberis strain SPOF3K, isolated from the kidney of a diseased olive flounder in South Korea in 2013. Sequencing using a PacBio platform yielded a circular chromosome of 2,128,740 bp and a plasmid of 23,538 bp, harboring 2,123 and 24 protein-coding genes, respectively.